2010
DOI: 10.1097/qad.0b013e328337b0ab
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 viral protein r induces ERK and caspase-8-dependent apoptosis in renal tubular epithelial cells

Abstract: Objective HIV-associated nephropathy is the most common cause of end stage renal disease in persons with HIV/AIDS and is characterized by focal glomerulosclerosis and dysregulated renal tubular epithelial cell (RTEC) proliferation and apoptosis. HIV-1 viral protein r (Vpr) has been implicated in HIV-induced RTEC apoptosis but the mechanisms of Vpr-induced RTEC apoptosis are unknown. The aim of this study was therefore to determine the mechanisms of Vpr-induced apoptosis in RTEC. Methods Apoptosis and caspase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 43 publications
0
41
0
Order By: Relevance
“…Vpr---mediated apoptosis is complex and appears to invoke cell death via multiple pathways. Previous studies in have identified caspase activation and mitochondrial injury as a key component cell death in Vpr+ RTECs [138,139]. Thus, mitotic cell death is a novel mechanism of Vpr---induced apoptosis in RTECs in vitro, and my demonstration of high levels of mitotic marker PH3 in murine and human HIVAN kidney biopsies suggest mitotic progression may be relevant to HIV pathogenesis in vivo.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Vpr---mediated apoptosis is complex and appears to invoke cell death via multiple pathways. Previous studies in have identified caspase activation and mitochondrial injury as a key component cell death in Vpr+ RTECs [138,139]. Thus, mitotic cell death is a novel mechanism of Vpr---induced apoptosis in RTECs in vitro, and my demonstration of high levels of mitotic marker PH3 in murine and human HIVAN kidney biopsies suggest mitotic progression may be relevant to HIV pathogenesis in vivo.…”
Section: Discussionmentioning
confidence: 86%
“…Vpr---mediated arrest in the G2 phase of the cell cycle is well established in both immortalized and primary renal tubule epithelial cells [60,138,139]. Previous work using pseudotyped lentiviral particles expressing single---gene constructs, pHR---Vpr, pHR---Tat, or pHR---Vif, confirm that the G2 arrest phenotype is Vpr---specific in RTEC model systems [60].…”
Section: Mechanisms Of Vpr-induced G 2 Arrest In the Kidneymentioning
confidence: 81%
See 1 more Smart Citation
“…Two major apoptotic pathways exploited by cells were discovered as an extrinsic or intrinsic pathway (31) by apical activation of caspase-8 or caspase-9, respectively. Early observations in various cell types showed that Vpr induced apoptosis either via the extrinsic pathway or intrinsic pathway (32)(33)(34)(35). Cell type-specific variations and context may account for these discrepancies (36).…”
Section: Discussionmentioning
confidence: 99%
“…Its expression in tubular epithelial cells is associated with G2 cell cycle arrest, impaired cytokinesis and finally apoptosis (Zhong et al, 2005;Rosenstiel et al, 2008;2009b;Snyder et al, 2010;Vashistha et al, 2008). A synergistic effect of nef and vpr was observed in a study which showed that mice with both nef and vpr expression developed more severe nephropathy (Zuo et al, 2006).…”
Section: Amjmentioning
confidence: 99%